2019
DOI: 10.33862/citradelima.v3i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Pendidikan Kesehatan Menggunakan Media Audio Visual dan Poster terhadap Perilaku Ibu Primipara dalam Manajemen Laktasi

Abstract: ASI merupakan cairan emulsi lemak yang dihasilkan dari kelenjar mamae pada ibu menyusui. Ibu primipara yang memberikan ASI tidak tahu tentang cara menyusui dengan benar dan tidak mengetahui cara memerah ASI. Pendidikan kesehatan manajemen laktasi pada ibu primipara penting untuk merubah perilaku ibu primipara yang menyusui. Media yang digunakan audio visual dan Poster. Penelitian ini bertujuan untuk mengetahui pengaruh pendidikan kesehatan menggunakan media audio visual dan poster terhadap perilaku ibu primipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
0
0
3
Order By: Relevance
“…Whereas the group with audiovisual media which contains the same material as posters but in the form of sound and video animation, the use of audiovisual media which involves the senses such as hearing and sight can affect the level of retention (absorption and memory) of the material presented, with audiovisual media the respondents were more interested, easy to remember and easy to understand. This research is in line with research conducted by previous study conducted at the Taman Krocok Community Health Center found that the audiovisual group had a higher average score than the poster group (Sholehah et al, 2020). Thus, it can be interpreted that health education methods using audiovisual media are more effective in improving the behavior of primiparous mothers in lactation management.…”
Section: Differences In Providing Education Using Poster Media and Au...supporting
confidence: 90%
“…Whereas the group with audiovisual media which contains the same material as posters but in the form of sound and video animation, the use of audiovisual media which involves the senses such as hearing and sight can affect the level of retention (absorption and memory) of the material presented, with audiovisual media the respondents were more interested, easy to remember and easy to understand. This research is in line with research conducted by previous study conducted at the Taman Krocok Community Health Center found that the audiovisual group had a higher average score than the poster group (Sholehah et al, 2020). Thus, it can be interpreted that health education methods using audiovisual media are more effective in improving the behavior of primiparous mothers in lactation management.…”
Section: Differences In Providing Education Using Poster Media and Au...supporting
confidence: 90%
“…Dengan kesimpulan dari hasil penelitian adalah ada pengaruh perilaku ibu primipara dalam manajemen laktasi sebelum dan sesudah dilakukan pendidikan kesehatan pada kelompok audio visual dan poster. 21 RS Khusus Bedah Columbia Asia adalah Rumah Sakit Khusus Bedah tipe A yang sudah berdiri sejak tahun 2014. Salah satu layanan dari Rumah Sakit Khusus Bedah Columbia Asia adalah jenis operasi seksio sesarea dengan metode ERACS.…”
Section: Pendahuluanunclassified
“…Kemudian dilanjutkan pertumbuhan serta perkembangan bayi diperlukan pemberian secara eksklusif hingga usia bayi 2 tahun [13]. Diberikanya ASI Eksklusif 0-6 bulan yaitu mencegah resiko kematian bayi, obesitas, dan kanker [14]. Kristiyanasari (2014), Mufdlilah, Subijanto, Sutisna & Akhyar (2017) menjelaskan bahwa manfaat ASI dibagi menjadi empat macam yaitu manfaat bagi ibu bisa membantu menunda kehamilan, manfaat bagi bayi bisa membantu untuk memulainya kehidupan supaya lebih baik, manfaat bagi keluarga yaitu proses laktasi sangat praktis bisa diberikan waktu kapan saja, dan manfaat bagi negara yaitu dapat mengurangi kejadian resiko angka kematian pada bayi [15].…”
Section: Literature Reviewunclassified